THE HYPOGLYCAEMIC EFFECT OF OLEANONIC ACID ISOLATED FROM PILEA ELIZABETHAE IN A RAT MODEL - ALEXANDER-LINDO, RUBY; Salmon, Coleen; Mcgrowder, Donovan (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of this study is to isolate and identify the chief hypoglycaemic component of Pilea elizabethae Methods: The chief hypoglycaemic component of Pilea elizabethaewas isolated and identified. The bio-directed purification of the chief hypoglycaemic agents contained in Pilea elizabethae followed a sequence of steps alternating oral glucose tolerance test (OGTT) bioassay and chromatographic methods. The ethyl acetate crude extract which was most hypoglycaemic in activity was flash chromatographed on silica gel using a gradient hexane-ethyl acetate solvent system of increasing polarity. Elucidation of the chemical structures of R-E2Gii was determined using NMR and FT-IR spectroscopy, melting point determination and comparison with literature. The Pilea elizabethae extracts were tested for hypoglycaemic activity in Sprague-Dawley albino rats using the oral glucose tolerance test (OGTT) method. Isolated hypoglycaemic compounds obtained after bio-directed purification were identified through nuclear magnetic resonance (NMR) spectroscopy and infra-red (IR) spectroscopy. Results: Bio-directed purification of Pilea elizabethae extracts yielded a hypoglycaemic principle that were coded R-E2Gii. By comparison of its NMR chemical shift values and physical properties with literature values, R-E2Gii found to be the triterpenoid oleanonic acid [C30H40O3; M. W=124]. The isolate R-E2Gii demonstrated significant hypoglycaemic activity. When administered intravenously, values were as low as 4.87Â±0.09 mmol/l thirty minutes post-load compared with 5.63Â±0.19 mmol/l for the control (p<0.006). An increase in dosage up to 10 mg/kg body weight amplified the post-prandial hypoglycaemic effect of R-E2Gii. Comparison of the hypoglycaemic effect of R-E2Gii with glibenclamide showed that the isolate was only mildly effective in reducing post-prandial hyperglycaemia. Hexane-ethyl acetate extracts from Pilea elizabethae was found to possess anti-hyperglycaemicactivity on OGTT. Conclusion: Bio-directed purification of the hexane-ethyl acetate extracts and using nuclear magnetic resonance (NMR) spectroscopy and infra-red (IR) spectroscopy revealed oleanonic acid, that may be responsible for the anti-hyperglycaemic properties of this extract.